Biomechanical evaluation of an autologous flexor digitorum lateralis graft to augment the surgical repair of gastrocnemius tendon laceration in a canine ex vivo model. Issue 8 (14th June 2020) - Duffy, Daniel J.; Curcillo, Chiara P.; Chang, Yi‐Jen; Gaffney, Lewis; Fisher, Matthew B.; Moore, George E.
Abstract: Objective: To evaluate the effect of an autologous flexor digitorum lateralis (FDL) graft to augment a three‐loop pulley (3LP) core repair in a canine cadaveric gastrocnemius tendon (GT) laceration model. Study design: Ex vivo, biomechanical study. Sample population: Twenty‐six canine cadaveric hind limbs. Methods: Tendons were divided into two groups (n = 13). After sharp transection, paired GT were repaired with 3LP or 3LP + FDL tendon augmentation. Yield, peak and failure loads, tensile loads required to create 1 and 3‐mm gapping, and failure modes were analyzed. Significance was set at P < .05. Results: Yield and failure force (mean ± SD) for 3LP + FDL were 134.9 ± 44.1 N and 205.4 ± 46.4 N, respectively, which were greater than for 3LP alone (67.9 ± 12.2 N and 91.8 ± 9.9 N, respectively, P < .0001). No constructs (0%) formed 1 or 3‐mm gaps in the 3LP + FDL graft group compared with 84% and 39% for 3LP, respectively ( P < .0001). Failure modes were different between groups ( P < .001), with 85% of 3LP + FDL constructs failing by tissue rupture at the myotendinous junction, distant to the repair site. Conclusion: Addition of an autologous FDL graft to a core 3LP tendon repair increased yield, peak, and failure forces by twofold, 2.3‐fold, and 2.2‐fold, respectively, compared with core 3LP alone while preventing the occurrence of gap formation. Clinical significance: Use of FDL tendon augmentation for GT laceration may increase repair site strength and resist gap formation better than 3LP core suture use alone. Additional studies are required in vivo to determine the effect of FDL graft augmentation on clinical function.